Sistem Informasi Penjualan Spareparts Alat Berat Berbasis Web Pada CV. Mitra Prima Lestari Jakarta - Irmayani Ningsih - Universitas Nusa Mandiri; Rame Santoso - Universitas Bina Sarana Informatika (Indonesian Journal of Networking and Security (IJNS), 2022)
Abstract - Online sales or e-commerce business is a separate mechanism since it was still young corn, but here is the special side. For the first time all humans on earth have an equal opportunity to be the same succeed in business inside the virtual world. The purpose of this study is to provide a heavy equipment spareparts sales application that is connected directly to the website complete with heavy equipments spareparts sales information and pricing, and how to purchase and to make it easier for users to search by special specification heavy equipment spareparts. The method that used in this thesis is the waterfall method which include communication planning, modeling, construction, and deployment. By using UML modeling. Results achieved in the form of a web-based application that can search for heavy equpment spareparts, as well as provide information needed for the reservation, such as information heavy equipment spareparts nearby. The conclusions obtained from this thesis is an online sales application on the website which can be used for shopping easier because heavy equipment spareparts featuring the image of spareparts as well as prices and how to purchase and specifications. Keywords - Sales Information Systems, Heavy Equipment, Spareparts Abstrak - Penjualan online atau e-commerce merupakan mekanisme bisnis tersendiri yang usianya masih seumur jagung. Namun disinilah sisi keistimewaanya. Untuk pertama kalinya seluruh manusia di muka bumi memiliki kesempatan yang sama agar dapat berhasil dalam bisnis di dunia maya. Tujuan penelitian ini adalah menyediakan aplikasi penjualan spareparts alat berat yang terhubung langsung ke website secara lengkap dengan informasi penjualan spareparts alat berat beserta harga dan cara pembeliannya sehingga dapat mempermudah user mencari spareparts alat berat dengan spesifikasi tertentu. Metode penelitian yang digunakan dalam skripsi ini adalah metode waterfall yang meliputi komunikasi perencanaan, pemodelan, konstruksi, dan deployment. Dengan menggunakan permodelan UML. Hasil yang dicapai berupa suatu aplikasi berbasis website yang dapat mencari spareparts alat berat serta memberikan informasi-informasi yang dibutuhkan untuk pemesanan tersebut, seperti info spareparts alat berat terdekat. Simpulan yang didapat dari penulisan skripsi ini adalah sebuah aplikasi penjualan online pada website yang bisa digunakan untuk belanja spareparts alat berat lebih mudah karena menampilkan gambar spareparts alat berat serta harga dan cara pembelian dan spesifikasi. Kata Kunci: sistem informasi penjualan, alat berat, spareparts